2020
DOI: 10.1007/s00779-020-01452-w
|View full text |Cite
|
Sign up to set email alerts
|

Designing everyday automation with well-being in mind

Abstract: Nowadays, automation not only permeates industry but also becomes a substantial part of our private, everyday lives. Driven by the idea of increased convenience and more time for the “important things in life,” automation relieves us from many daily chores—robots vacuum floors and automated coffee makers produce supposedly barista-quality coffee on the press of a button. In many cases, these offers are embraced by people without further questioning. However, while we save time by delegating more and more every… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…This turned it into a platform carrier to building a harmonious group relationship. In Hassenzahl's [30] research, they found that meaningful moments of happiness can be increased by creating common interests and prolonging the process of experience.…”
Section: Discussionmentioning
confidence: 99%
“…This turned it into a platform carrier to building a harmonious group relationship. In Hassenzahl's [30] research, they found that meaningful moments of happiness can be increased by creating common interests and prolonging the process of experience.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we administered the Positive and Negative Affect Schedule (PANAS; Watson et al, 1988 ; German translation by Krohne et al, 1996 ) to assess this facet of subjective wellbeing. It has been found to be a reliable and valid measure ( Crawford and Henry, 2004 ) and is well established in HCI and UX research (e.g., Hassenzahl, 2008b ; Partala and Kallinen, 2012 ; Anderson et al, 2017 ; Klapperich et al, 2020 ). Another reason for choosing PANAS over other measures was the fact that it allows for capturing positive and negative emotions separately.…”
Section: Methodsmentioning
confidence: 99%
“…Second, his focus on performance and audience emphasizes social motives for certain activities, but neglects non-social motives. These have been studied previously in psychology and HCI for individual interactions and experiences [7,12,13,22,41]. Third, the understanding of intentional and unintentional communication helps to describe social settings and explains how social interactions unfold.…”
Section: The Dramaturgical Modelmentioning
confidence: 99%
“…In addition, the family breakfast scenario indicates how changes in material (addition of a loudspeaker/removal of a wire) can allow for new dynamics between co-located practices that can complement each other. Methods and case studies for the analysis of single practices already exist (e.g., [9,19,22,27,29,44]). These can serve as a basis for further research on positive relations between multiple practices.…”
Section: Applications and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation